Discretion and Public Procurement Outcomes in Europe - Bernard Hoekman; Bedri Kamil Onur Taş (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2023)
Public procurement regulations aim to ensure the state obtains 'value for money' by specifying the processes to be used in issuing calls for tender and award of contracts. Value for money goals may be complemented by ancillary objectives such as supporting small or disadvantaged firms. Recent theory suggests procurement regulations constraining the ability to exercise discretion in awarding contracts may increase average procurement costs in countries with high levels of government effectiveness. Using detailed data on procurement awards in 33 European countries, we find a positive, significant relationship between more restrictive practice towards exercise of discretion in procurement awards and average contract prices that increases in countries with above average government effectiveness. We also show that realizing efficiency benefits from exercising greater discretion where permitted by law reduces the probability small firms win contracts and continue to do so, pointing to a tradeoff between the potential cost reduction benefits of exercising discretion and other goals of procurement policy.
Keywords: H57; O31; O32; 330; Public procurement; contract prices; discretion; SMEs; government effectiveness